Tourism Demand in the Kingdom of Bahrain - Abdella, Nour (2010)
In Bahrain, international tourism has increased significantly in the last decade, which makes the study of the tourism demand very important to know if there are any direct effect between the increase of demand and other factors connected to the tourism sector. In this research paper there will be a tourism demand analysis on the Kingdom of Bahrain from 1998 to 2010 and what changes happened within those 12 years. Kingdom of Bahrain is one of countries that are increasing in demand of tourism especially the use of events to attract the eyes to it, and this will be shown through the analysis of the data that has been collected with the different changes that happened in the last decade and additionally using a theoretical model the causal chain effect to implement those event and to see the decisions of a rational visitor when deciding to visit a destination and to locate which type of visitors are attracted and which event attracts the most.